Clinical Outcome of Minor Salivary Gland Cancers in the Oral Cavity: A Comparative Analysis With Squamous Cell Carcinomas of the Oral Cavity - Park, Song I; Park, Woori; Choi, Sungyong; Jang, Yunjeong; Kim, Hyunjin; Kim, Seok-Hyung; Noh, Jae Myoung; Chung, Man Ki; Son, Young-Ik; Baek, Chung-Hwan; Jeong, Han-Sin (Frontiers in Oncology, 2020)
Purpose: Salivary gland cancer (SGC) in the oral cavity is not common and has been less studied in comparison with oral squamous cell carcinoma (SCC). This study aimed to identify the clinical characteristics and outcomes of SGC in the oral cavity compared with oral SCC. Methods: The medical charts of the patients with SGC (N = 68) arising from minor salivary glands and SCC (N = 750) in the oral cavity between 1995 and 2017 were reviewed retrospectively. The clinical and pathological factors and treatment outcomes were compared to identify clinical differences between oral SGC and SCC in total cases and in tumor size and subsite (propensity score)-matched pairs (N = 68 in each group). In addition, pattern of local invasion was pathologically assessed in a subset of SGC and SCC tumors. Results: Patients with SGC in the oral cavity showed >90% survival at 5 years. Most common pathologies of SGC were mucoepidermoid carcinoma (39.7%) and adenoid cystic carcinoma (35.3%), where high-grade tumors (including adenoid cystic carcinomas having solid components, grade 2 or 3) represented only 36.8%. Compared with oral SCC, surgery for SGC had narrow surgical safety margin. However, local control was very successful in SGC even with <5 mm or positive resection margin through surgery plus adjuvant radiation treatments or surgery alone for small low-grade tumors. Pathologic analysis revealed that the frequency of oral SGC with infiltrative tumor border was significantly lower than that of oral SCC (46.4 vs. 87.2%, P < 0.001). Conclusions: SGC in the oral cavity represents relatively good prognosis and has a locally less aggressive pathology compared with oral SCC. Adjuvant radiation can be very effective to control minimal residual disease in oral SGC. Our study proposed that a different treatment strategy for oral SGC would be reasonable in comparison with oral SCC.